A collaborative approach to eating disorders - Alexander, June, 1950-; Treasure, Janet (London : Routledge, 2012)
'While many aspects of eating disorders remain a mystery, there is growing evidence that collaboration is an essential element for treatment success. This book emphasises and explains the importance of family involvement as part of a unified team approach towards treatment and recovery. A Collaborative Approach to Eating Disorders draws on up-to-date evidence based research as well as case studies and clinical vignettes to illustrate the seriousness of eating disorders and the impact on both the sufferer and their loved ones. Areas of discussion include: -current research including genetic factors, socio-cultural influences and early intervention -clinical applications such as family based dialectical and cognitive behavioural treatments -treatment developments for both adolescents and adults with a range of eating disorders -building collaborative alliances at all levels for treatment and ongoing recovery. With contributions from key international figures in the field, this book will be a valuable resource for students and mental health professionals including family doctors, clinicians, nurses, family therapists, dieticians and social workers'--Provided by publisher.
Introduction / Carrie Arnold -- The family context: cause, effect or resource / Anna Konstantellou, Mari Campbell and Ivan Eisler -- The links between genes and the environment in the shaping of personality / Janet Treasure and Natalie Kanakam -- Neurobiology explanations for puzzling behaviours / Walter H. Kaye, Ursula F. Bailer and Megan Klabunde -- Emotions and empathic understanding: capitalizing on relationships in those with eating disorders / Nancy Zucker [and others] -- Modifiable risk factors that can be translated into prevention or resilience / Susan J. Paxton -- Obesity and eating disorders / Emma Dove and Susan Byrne -- Introduction / Laura (Collins) Lyster-Mensh -- Physical effects of eating disorders / C. Laird Birmingham -- The role of nutrition: what has food got to do with it? / Susan Hart [and others] -- Pharmacotherapy of eating disorders / Leora David, Allegra Broft and B. Timothy Walsh -- Psychotherapies in eating disorders / Tracey D. Wade and Hunna J. Watson -- Families as an integral part of the treatment team: treatment culture and standard of care challenges / Renee Rienecke Hoste, Angela Celio Doyle and Daniel le Grange -- Effectively engaging the family in treatment / Stephanie Milstein and Carrie Arnold -- Involving careers: a skills-based learning approach / Elizabeth Goddard, Simone Raenker and Janet Treasure -- The therapeutic alliance in cognitive behavioural therapy for adults with eating disorders / Jane Evans and Glenn Waller -- Integrating dialectical behaviour therapy and family-based treatment for multidiagnostic adolescent patients / Anita Federici and Lucene Wisniewski -- Couples therapy for anorexia nervosa / Cynthia M. Bulik, Donald H. Baucom and Jennifer S. Kirby -- Relapse prevention / Marion P. Olmsted, Jacqueline C. Carter and Kathleen M. Pike -- Introduction / Eric van Furth -- Childhood and adulthood: when do eating disorders start and do treatments differ? / Peter M. Doyle, Angela Smyth and Daniel le Grange -- Recognising and diagnosing early onset eating disorders / Sloane Madden -- Food phobia of childhood / Julie O'Toole -- Unravelling binge eating disorder / Angica M. Claudino and Christina M. Morgan -- Eating disorders in women of African descent / Stefanie Gilbert -- Eating disorders and athletes / Jorunn Sundgot-Borgen and Solfrid Bratland-Sanda -- Male eating disorders / John F. Morgan -- Introduction / Claire Vickery -- Narrowing the psychotherapy research-practice gap / Kristin M. von Ranson and Ann M. Laverty -- Why carers need to know about research / Susan Ringwood -- Promoting a full agenda of rights / Lynn S. Grefe -- The patient-family-clinician-researcher quest for quality care / Mary Tantillo.
Includes bibliographical references and index.
Keywords: Eating Disorders -- psychology; Eating Disorders -- therapy; Family Relations; Family Therapy -- methods; Professional-Patient Relations